2003
DOI: 10.1103/physrevb.67.113103
|View full text |Cite
|
Sign up to set email alerts
|

Strong spatial dispersion in wire media in the very large wavelength limit

Abstract: It is found that there exist composite media that exhibit strong spatial dispersion even in the very large wavelength limit. This follows from the study of lattices of ideally conducting parallel thin wires ͑wire media͒. In fact, our analysis reveals that the description of this medium by means of a local dispersive uniaxial dielectric tensor is not complete, leading to unphysical results for the propagation of electromagnetic waves at any frequencies. Since nonlocal constitutive relations have been usually co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
414
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 584 publications
(430 citation statements)
references
References 13 publications
14
414
0
2
Order By: Relevance
“…1(a) has been described for an incident electric field parallel to the wires as an artificial dielectric [18][19][20] with an isotropic effective plasma-like relative permittivity ε eff r = 1 − f 2 P /f 2 , where f is the signal frequency, f p is the plasma frequency which depends on the wire diameter and interspacing, see [21][22][23][24] (such medium is assumed to be lossless, which is a reasonable approximation at microwave frequencies). Spatial dispersion should be additionally taken into account when the waves travel at a slant angle to the wire axes [25,26]. For waves propagating normally to the wires, and in the absence of losses, a homogenized wire medium exhibits negative effective permittivity at f < f p (see Fig.…”
Section: Background Electric and Magnetic Resonances In Wire And Srrmentioning
confidence: 99%
“…1(a) has been described for an incident electric field parallel to the wires as an artificial dielectric [18][19][20] with an isotropic effective plasma-like relative permittivity ε eff r = 1 − f 2 P /f 2 , where f is the signal frequency, f p is the plasma frequency which depends on the wire diameter and interspacing, see [21][22][23][24] (such medium is assumed to be lossless, which is a reasonable approximation at microwave frequencies). Spatial dispersion should be additionally taken into account when the waves travel at a slant angle to the wire axes [25,26]. For waves propagating normally to the wires, and in the absence of losses, a homogenized wire medium exhibits negative effective permittivity at f < f p (see Fig.…”
Section: Background Electric and Magnetic Resonances In Wire And Srrmentioning
confidence: 99%
“…An excellent possibility to realize the canalization regime for p-polarization is provided by a wire medium, a material formed by a lattice of parallel conducting wires [30,31,32,33]. This material supports very special type of eigenmodes, so-called transmission line modes [33], which transfer energy strictly along wires with the speed of light and can have arbitrary transverse wave vector components.…”
mentioning
confidence: 99%
“…This material supports very special type of eigenmodes, so-called transmission line modes [33], which transfer energy strictly along wires with the speed of light and can have arbitrary transverse wave vector components. It means that such modes correspond to completely flat isofrequency contour which is the main requirement for implementing the canalization regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The wire mesh has a period a, and the wires have radius r w . It has been shown that a general wire medium (single, double or triple) suffers from a spatial dispersion [10], [11], nevertheless it can be considered as an isotropic negative permittivity medium near the plasma frequency [12]. A spatial dispersion can be defined as a nonlocal dispersive behavior of the material, i.e., the constitutive permittivity and permeability tensors depend not only on the frequency, but also on the spatial derivatives of the electric and magnetic field vectors or, for plane electromagnetic waves, on the wave-vector components determining the direction of propagation.…”
Section: Introductionmentioning
confidence: 99%